Steady-state heat transfer to pseudoplastic fluid food in pipe flow - Ahmed Salih, Elzubier (Federation of Engineering Institutions of Islamic Countries, 2006)
The results of numerical simulation of heat transfer to power-law fluids with variable rheology flowing in a cylindrical tube under uniform heat flux at the wall are compared with the results of published experimental study and an established correlation [7]. used CMC(Carboxymethylecellulose) solution and Tomato juice as working fluids. Physical properties of tests fluids were assumed to be temperature dependant. The effect of natural convection was checked and considered negligible. The FLUENT6.1 Package has been used for simulation. The computational model is briefly described. In particular heat transfer coefficients obtained from the calculated temperature profiles and compared with published for CMC solution and tomato juice flows.